PULSE PRESSURE CLASSES AND DOSAGE OF THE MAIN GROUPS OF CARDIAC MEDICATIONS IN PATIENTS AT THE ANNUAL FOLLOW-UP PERIOD AFTER PACING - Pochinska, M. V.; Shevchuk, M. I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2017)
Dose factor of the main groups of cardiac medications in five pulse pressure (PP) classes was studied in 220 patients (110 men and 110 women) at the annual stage after pacing, the average age 70 ± 9 years. Patients with the IV and V class of PP require the administration of higher doses of antiarrhythmics, diuretics, calcium channel blockers and ACE inhibitors. In patients after pacing, the dose factor of the main groups of cardiac medications correlates with the PP classes and, the greater the PP class, the greater the dose rate of the medications. After pacing an increase of the dose factor of antiarrhythmic drugs (amiodarone) in the early period and diuretics and ß-blockers throughout the observation period with an increase in the PP class is required. The long term period of pacing contribute to reduction of the dose factor of antiarrhythmic drugs (amiodarone), Ca-channel blockers and ACE inhibitors in all classes of PP, to a greater extent - in II and III classes. The dose factor of anticoagulants, antiplatelet agents, ARBs and HMG CoA reductase inhibitors does not depend on the PP class and does not change over the entire observation period. Patients after pacing with IV and V classes of PP require the higher doses of antiarrhythmics, diuretics, Ca-channel blockers and ACE inhibitors.